2007
DOI: 10.1128/aem.00169-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals that Multidrug Efflux Genes Are Upregulated To Protect Pseudomonas aeruginosa from Pentachlorophenol Stress

Abstract: Through chemical contamination of natural environments, microbial communities are exposed to many different types of chemical stressors; however, research on whole-genome responses to this contaminant stress is limited. This study examined the transcriptome response of a common soil bacterium, Pseudomonas aeruginosa, to the common environmental contaminant pentachlorophenol (PCP). Cells were grown in chemostats at a low growth rate to obtain substrate-limited, steady-state, balanced-growth conditions. The PCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 56 publications
8
43
1
Order By: Relevance
“…Microbiological stress responses have been observed on exposure to many environmentally relevant chemicals, including phenols [1], chlorophenols [2,3], dinitrophenols [4,5], toluene [6], methyltert-butyl ether [7], explosive 2,4,6-Trinitrotoluene [8], explosive cyclotrimethylenetrinitramine [9], and dibenzo-p-dioxin [10]. Microorganisms that are effective at degrading pollutants can be stressed by exposure to these chemicals, as has been observed for Methylocystis sp.…”
Section: Introductionmentioning
confidence: 93%
“…Microbiological stress responses have been observed on exposure to many environmentally relevant chemicals, including phenols [1], chlorophenols [2,3], dinitrophenols [4,5], toluene [6], methyltert-butyl ether [7], explosive 2,4,6-Trinitrotoluene [8], explosive cyclotrimethylenetrinitramine [9], and dibenzo-p-dioxin [10]. Microorganisms that are effective at degrading pollutants can be stressed by exposure to these chemicals, as has been observed for Methylocystis sp.…”
Section: Introductionmentioning
confidence: 93%
“…Unless mutations disrupt the nalC (PA3721) gene, which encodes a TetR family regulator (727) that strongly represses the adjacent PA3720-PA3719 operon, baseline amounts of ArmR are not expected to influence MexAB-OprM production in wild-type cells (406). However, chemostat experiments with strain PAO1 showed that various chlorinated phenols, including the environmental contaminant pentachlorophenol, can induce the expression of the PA3720-PA3719 and mexAB-oprM operons through reversible, noncovalent binding to the NalC protein (807,808). Recent data, however, showed that pentachlorophenol stimulates MexABOprM production, surprisingly, in an ArmR-independent (although MexR-dependent) manner (809).…”
Section: P Aeruginosa Efflux Pumpsmentioning
confidence: 99%
“…The best-characterized efflux system in P. aeruginosa is MexAB-OprM, which displays an expansive substrate profile that includes not only antibiotics and biocides, but organic solvents, dyes, detergents, and homoserine lactones involved in quorum sensing (3). Although pentachlorophenol exposure appears to up-regulate mexAB-oprM (6), expression of these efflux genes is generally considered constitutive in wild-type (WT) strains. However, mutations in any of three regulatory genes, mexR (7,8), nalC (9,10), or nalD (11), have been shown to cause hyperexpression of mexAB-oprM and increased resistance to various medically relevant antimicrobials (11,12).…”
mentioning
confidence: 99%